Upaya Meningkatkan Pemahaman Santri pada Pembelajaran Fiqih Thaharah melalui Media Audio Visual - Fathor Rozi; Ummi Hanik Alawiyah (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
TPQ Al-Istiqomah in the process of learning fiqh thaharah uses the lecture method. The use of the lecture method is deemed ineffective to use in the delivery of this thaharah material, because santri tend to be bored, sleepy and less focused, besides that there are some materials in thaharah that are needed by santri concentration in the process of understanding. Therefore it takes a method or learning media that is more attractive and appropriate to the age of the santri, the media is an audio-visual learning media, this media will awaken more of the santri senses in the learning process. The purpose of this research is to improve the learning of thaharah fiqh material for santri so that they can understand thaharah and can practice and practice it in everyday life. The conclusion of this study is that it is proven that the use of audio-visual learning media is proven to be more effective in increasing understanding of the learning material of fiqh thaharah compared to the previous learning method, namely lectures. This is evident from the results of the evaluation of the students' learning at the end of the lesson in the form of prayer reading, memorization and practice.